Constructing Multicultural Narratives: A Study of Attitudinal Themes in Upin & Ipin’s Religious Festival Episodes - Sari, Rosita (Islamic Thought Review, 2024)
This study explores the portrayal of attitudes towards religious multiculturalism in the animated series Upin & Ipin, focusing on episodes centered around Hari Raya, Deepavali, and Gong Xi Fa Cai. Given the rich diversity present in human societies, understanding how media representations handle multicultural interactions is crucial. Utilizing a qualitative approach, this research conducts a library-based analysis of historical and philosophical concepts related to multiculturalism. The investigation aims to examine and interpret the series' depiction of attitudes towards religious diversity and their practical implications for multicultural interactions. The findings reveal four key attitudes promoted within the series: tolerance, harmony, fairness, and respect. These attitudes are not only depicted within the series but also reflect practices that can be applied to real-world multicultural contexts. The study concludes that these attitudes are not merely fictional portrayals but reflect practical approaches that can be applied in real-world multicultural settings. Upin & Ipin serves as a model for fostering positive intercultural relationships by illustrating how empathetic and respectful interactions can contribute to a more harmonious society. The series provides an effective framework for addressing and navigating religious diversity, offering valuable lessons for both individuals and communities striving to cultivate inclusive and supportive environments.